Construction and analysis of puncture clamp model for 10KV insulation line based on finite element. (August 2019) - Wu, Shaolei; Feng, Yu; Shi, Xun; Zhang, Xu; Huang, Peng
Abstract: At present, the puncture clamp has been widely used in the cable branching technology. However, due to the complicated installation process, the clamping force is too large during installation, resulting in cable damage and reduced life. If the clamping force is too small, it may cause poor contact or even cause fire. In this paper, the 3D solid model of the puncture clamp is established by using SolidWorks 3D software. Then the finite element analysis model of the puncture clamp is established in the finite element analysis software ANSYS Workbench, and the static analysis and exploration of the puncture clamp are obtained. The results show that the puncture blade and the conductor on the puncture clamp have the greatest contact stress and the maximum amount of deformation of the bolt, while the bolt meets the required strength. The results can be used to further optimize the structural design of the puncture clamps, refine the installation specifications and guide the installation.